205. Reduction of Antibiotic Prescribing Within a Veterans Affairs Emergency Department Through Peer Comparison. (26th November 2018) - Phulpoto, Rameez; Shively, Nathan R; Buehrle, Deanna J; Clancy, Cornelius J; Decker, Brooke K
Abstract: Background: Reduction in inappropriate antibiotic use in Emergency Departments can have a major impact on overall outpatient antibiotic use. Peer comparison has been used to successfully reduce antibiotic prescribing in primary care clinics at our hospitals and others. Methods: An educational session was held for Emergency Department physicians (EDPs) at VA Pittsburgh. EDPs were then sent monthly comparison charts of their oral antibiotic prescribing rates as well as peer rates. An intervention period of January–March 2018 was compared with a seasonal baseline of the same months in 2017. A random sample of oral antibiotic prescriptions was reviewed in-depth for adherence to consensus guidelines. Results: During the baseline period of January–March 2017, 427 oral antibiotic prescriptions were written by 16 EDPs during a total of 3, 722 patient encounters, with an antibiotic prescription index of 114.1 per 1, 000 patient encounters. In comparison, 301 prescriptions were written by the same 16 EDPs during 4, 874 patient encounters in the postintervention period (January–March 2018), with an antibiotic prescription index of 61.7 per 1, 000 patient encounters (45.9% decrease; P < 0.0001)). Azithromycin and fluoroquinolone indices decreased from 29.6 to 16.6 (43.9%; P < 0.0001) and 10.5 to 8.0 (23.8%; P = 0.2) per 1, 000 encounters, respectively. Among randomly reviewed prescriptions, there was a trend toward a decrease in inappropriate antibiotic prescribing from 47.6% (20/42) to 30% (9/30) ( P = 0.15). Among the randomly reviewed prescriptions that were indicated, there were non-significant decreases in the percentages of guideline-discordant agents (22.7% (5/22) to 14.2% (3/21; P = 0.7)), and in the percentage of guideline-concordant agents given for a guideline-discordant duration (29.4% (5/17) to 22.2% (4/18; P = 0.7)). Likewise, there were non-significant decreases in inappropriate antibiotic prescribing for URIs (94.1% (16/17) to 75% (3/4); P = 0.35). Conclusion: In an emergency department setting, initial education followed by monthly peer comparison of overall antibiotic prescribing rates significantly reduced overall antibiotic prescribing. Ongoing data review will reveal if trends toward reductions in inappropriate antibiotic prescribing are significant. Disclosures: All authors: No reported disclosures.